RISK FACTOR ANALYSIS OF STUNTING IN UNDER-FIVES AGED 24-59 MONTHS IN THE WORKING AREA OFPUSKESMAS MOTOLOHUKABUPATEN POHUWATO - Dewi Modjo; Andi Akifa Sudirman; Andriyadi Hasan (Jambura Journal of Health Sciences and Research, 2023)
Stunting merupakan kondisi pertumbuhan tinggi badan balita mengalami gangguan dimana tinggi badan balita tidak sesuai dengan usianya. Stunting atau tubuh pendek merupakan indikator jangka panjang untuk seorang balita yang mengalami kekurangan gizi dimana kejadian tersebut diakibatkan dari tumbuh kembang yang mengalami kegagalan dan kekurangan gizi kronis jangka panjang. Kebaruan penelitian ini karena meneliti tentang faktor risiko kejadian stunting pada balita usia 24-59 bulan. Penelitian ini bertujuan untuk menganalisis faktor risiko kejadian stunting pada balita usia 24-59 bulan di Wilayah Kerja Puskesmas Motolohu Kabupaten Pohuwato. Penelitian ini menggunakan jenis penelitian analitik observasional dengan menggunakan desain penelitian case control. Pengambilan sampel menggunakan total sampling dengan jumlah sampel 66. Pengumpulan data menggunakan lembar kuesioner dan obervasi. Analisis data menggunakan perhitungan Odds Ratio (OR) dan  uji Chi Square. Hasil penelitian didapatkan riwayat IMD (OR=7,703 dan p-value=0,001), riwayat pemberian ASI Eksklsuif (OR=14,063 dan p-value=0,000), riwayat pemberian MP-ASI (OR=8,543 dan p-value=0,000), jarak kelahiran ibu (OR=0,560 dan p-value=0,451),  tinggi badan ibu (OR=1,159 dan p-value=0,786) dan pekerjaan ibu (OR=1,611 dan p-value=0,492). Kesimpulan bahwa faktor risiko kejadian stunting pada balita adalah riwayat IMD, riwayat pemberian ASI Eksklusif, riwayat pemberian MP-ASI, tinggi badan ibu dan pekerjaan ibu.Kata Kunci : ASI ekslusif; IMD; Jarak kelahiran; MP-ASI; Tinggi badan; Stunting AbstractStunting is a condition of growth in the height of toddlers experiencing disorders where their size does not match their age. Stunting or short body is a long-term indicator for a malnourished toddler, where the event is caused by failure and long-term chronic malnutrition. The novelty of this study is that it examines the risk factors for stunting in toddlers aged 24-59 months. This study aims to analyze the risk factors for stunting in toddlers aged 24-59 months in the Motolohu Health Center Working Area, Pohuwato Regency. This study used observational analytical research using a case-control research design. Sampling used total sampling with a total sample count of 66. Data collection using questionnaire sheets and observation. Data analysis using Odds Ratio (OR) calculation and Chi-Square test. The results of the study obtained a history of IMD (OR=7,703 and p-value=0.001), a history of exclusive breastfeeding (OR=14,063 and p-value=0,000), a history of giving complementary foods (OR=8,543 and p-value=0.000), maternal birth distance (OR=0.560 and p-value=0.451), maternal height (OR=1.159 and p-value=0.786) and maternal work (OR=1,611 and p-value=0.492). The conclusion is that the risk factors for stunting in toddlers are IMD history, exclusive breastfeeding history, MP-ASI history, mother's height, and mother's occupation.Keywords: Exklusive breastfeeding; IMD; Birth spacing; MP-ASI; Height occupation; Stunting